Diversity of Crenosoma species in mustelids with the first molecular characterization of C. melesi and C. petrowi - Deak, Georgiana; Ionică, Angela Monica; Gherman, Calin Mircea; Mihalca, Andrei Daniel (Frontiers in Veterinary Science, 2023)
Species of genus Crenosoma have a wide distribution and are reported in Europe, the Americas, and Asia. Currently, the genus includes 14 nominal species, out of which 9 are parasitic in mustelids. Two species are mostly reported in mustelids from Europe, namely C. melesi and C. petrowi. Up to now, no genetic sequences are deposited in GenBank for any of the two. The aims of this study were to investigate the distribution, prevalence, and diversity of Crenosoma spp. infecting mustelids in Romania and to genetically characterize the species. Mustelids (n=247) were collected over a period of 7 years from different locations in Romania and the respiratory tract was removed and examined for nematodes. Detected nematodes were morphologically identified and fragments of two genes were sequenced. Sampled mustelids included Eurasian badger, Meles meles (n=102), Eurasian otter, Lutra lutra (n=20), beech marten, Martes foina (n=36), European pine marten, Martes martes (n=5), steppe polecat, Mustela eversmanii (n=1), European mink, Mustela lutreola (n=1), least weasel, Mustela nivalis (n=2), European polecat, Mustela putorius (n=78), and marbled polecat, Vormela peregusna (n=1). Nematodes from Eurasian badgers were morphologically identified as C. melesi (n=13, 12.74%) and C. petrowi (n=3, 2.94%). Nematodes from the beech martens were identified as C. petrowi (n=6, 16.66%), C. vulpis (n=1, 2.78%) and Crenosoma spp. (n=3, 8.33%). Co-infections with two Crenosoma species were detected in one beech marten (C. petrowi + C. vulpis, n=1, 2.77%) and in one European pine marten (C. petrowi + C. vulpis (n=1, 20%)). Two genes of Crenosoma melesi and C. petrowi were partly sequenced for the first time. We report new host-parasite associations for M. martes and C. vulpis. However, further studies are needed in order to determine the host-parasite associations and to improve the understanding of the epidemiology of Crenosoma nematodes.